2020
DOI: 10.1186/s12894-020-00739-7
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Skin rash following Administration of Apalutamide in Japanese patients with Advanced Prostate Cancer: an integrated analysis of the phase 3 SPARTAN and TITAN studies and a phase 1 open-label study

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…Are there any risk factors that predispose to drug eruptions caused by apalutamide? A number of clinical risk factors, including Eastern Cooperative Oncology Group Performance Status, baseline PSA, time from diagnosis to first dose, Gleason score, and previous treatment have been considered, but no definite risk factors have been found 4 . The exact reason why the incidence of drug eruption for apalutamide is higher in Japanese is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Are there any risk factors that predispose to drug eruptions caused by apalutamide? A number of clinical risk factors, including Eastern Cooperative Oncology Group Performance Status, baseline PSA, time from diagnosis to first dose, Gleason score, and previous treatment have been considered, but no definite risk factors have been found 4 . The exact reason why the incidence of drug eruption for apalutamide is higher in Japanese is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of skin rash was found to be higher in the apalutamide group than in the placebo group in both SPARTAN (23.8% vs. 5.5%) and TITAN (27.1% vs. 8.5%) 2,3 . Notably, a subgroup analysis of Japanese patients in both studies revealed that apalutamide-induced skin rash was more prevalent in the Japanese population than in the global population (56.0% vs. 0.0% in SPARTAN and 50.0% vs. 8.7% in TITAN) 4 . However, in both these studies, a wide variety of exanthemata was observed in patients treated with apalutamide, including maculopapular rash, butterfly rash, erythematous rash, generalized rash, papules, pruritic rash, pustular rash, lupus rash, erythema multiforme, stomatitis, and urticaria, which were grouped together as "rash" 2,3 .…”
Section: Introductionmentioning
confidence: 96%
“…Apalutamide is an androgen receptor inhibitor for treatment of castration‐resistant prostate cancer 2 . It has been reported that the Japanese population has a higher incidence of skin rashes caused by apalutamide, with five reported cases of toxic epidermal necrolysis (TEN), half of which were fatal (online supplementary Table S1) 3 . The correlation of human leukocyte antigen (HLA) typing with serious drug reactions like TEN is well established, but further studies are needed to explore the correlation between HLA typing with apalutamide‐related skin rash.…”
Section: Figurementioning
confidence: 99%
“…2 It has been reported that the Japanese population has a higher incidence of skin rashes caused by apalutamide, with five reported cases of toxic epidermal necrolysis (TEN), half of which were fatal (online supplementary Table S1). 3 The correlation of human leukocyte antigen (HLA) typing with serious drug reactions like TEN is well established, but further studies are needed to explore the correlation between HLA typing with apalutamide-related skin rash. According to previous studies, the median time from apalutamide initiation to the appearance of skin rash is 82 days.…”
Section: Dear Editorsmentioning
confidence: 99%
“…Apalutamid ist ein Androgenrezeptor‐Inhibitor zur Behandlung von kastrationsresistentem Prostatakrebs 2 . Es wurde berichtet, dass die japanische Bevölkerung eine höhere Inzidenz von durch Apalutamid verursachten Hautausschlägen aufweist, mit fünf gemeldeten Fällen von toxischer epidermaler Nekrolyse (TEN), von denen die Hälfte tödlich verlief (ergänzende Online‐Tabelle S1) 3 . Die Korrelation der Typisierung des humanen Leukozytenantigens (HLA) mit schweren Arzneimittelreaktionen wie TEN ist gut belegt, aber es sind weitere Studien erforderlich, um die Korrelation zwischen HLA‐Typisierung und apalutamidbedingtem Hautausschlag zu untersuchen.…”
Section: Abbildungunclassified